PARTICLES SWARM OPTIMIZATION FOR THE CRYPTANALYSIS OF TRANSPOSITION CIPHER - Hameed, Sarab M; Hmood, Dalal N (Al-Nahrain Journal of Science, 2010)
Transposition ciphers are a class of historical encryption algorithms based on rearranging unitsof plaintext according to some fixed permutation which acts as the secret key. This paper presents anew investigation for cryptanalysis transposition cipher based on Particle Swarm Optimization(PSO). PSO is utilized for the automatic recovery of the key, and hence the plaintext, from only thecipher text. Based upon a mathematical model of the social interactions of swarms, the algorithmhas been shown to be effective at finding good solutions. Experimental results show the ability ofPSO in finding the correct secret key which is used to recover the plaintext.